Teacher empowerment affecting morale related to work performance of teachers in schools under the office of Pathum Thani Primary Education Service Area 2 - Ontavorn, Dararat (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aim to 1. Study the level of teachers’ empowerment; 2) Identify the level of teachers’ morale in work performance; and 3. Analyze the teachers’ empowerment affecting teachers’ morale in work performance. The research sample, derived by proportional stratified random sampling as distributed by size, was 297 teachers of government schools under Pathum Thani Primary Educational Service Area Office 2. The research instrument was a questionnaire constructed by the researcher with IOC content between 0.67 and 1.00. The internal consistency reliability coefficients of the questionnaire: teachers’ empowerment was 0.97 and teachers’ morale in work performance was 0.94. Data were analyzed with percentage, mean, standard deviation and stepwise multiple regression. The research found that 1. Overall and in specific aspects, the teachers’ empowerment was at a high level. They were, ranked from the highest to the lowest, advancement, increase competence and skill, support, information, reward and recognition, and resources. 2. Overall and in specific aspects, the teachers’morale in work performance was at a high level. They were, ranked from the highest to the lowest, achievement, working condition, company policy and administration, and benefits and reward. 3. The teachers’empowerment in the aspects of increase competence and skill (X5), information (X2), advancement (X4), and reward and recognition (X6), together predicted the teachers’ morale in work performance (Ytot) ) at the percentage of 62.60 with statistical significance at .01. The regression equation was = 1.00 + 0.23 (X5) + 0.18 (X2) + 0.20 (X4) + 0.11 (X6). Article history : Received 6 Mar 2019 Revised 27 April 2019 Accepted 29 April 2019 SIMILARITY INDEX = 0.93